(untitled) (Plant Tissue Culture and Biotechnology, 2025)
In banana micropropagation, the most critical limiting factor is the rate of shoot multiplication. Due to high demand for plantlets in a particular season for cultivation, different commercial tissue culture laboratories are always under pressure for space, sterile area, energy, etc., to cope with targeted production of plantlets on time. The current method of shoot tip culture has a lot of limitations, and many Laminar Air Flow (LAF) operators are involved in TC banana production. Advanced techniques are required to be developed to produce millions of banana plantlets at a low cost. Maintenance of a high and constant multiplication rate is key to the success of a commercial Tissue Culture banana laboratory. There are various reasons for the low and non-consistent multiplication rate of the banana. This has been observed that during the in vitro culture the growth of the developing shoots was better in the vertical position than in the horizontal position of the shoot meristem. It shows that a change in the polarity of the explant delayed the growth in the semi-solid nutrient medium. Plant Tissue Cult. & Biotech. 35(1): 185-198, 2025 (June)